Differences in of Adolescent Girls Knowledge and Attitudes on Vulva Hygiene Before and After Health Education in Mojokerto Regency - Aulia Maharani; Indra Yuliati; Andriyanti Andriyanti; Dewi Setyowati (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Fluor albus or vaginal discharge is a common condition among adolescent girls and may be physiological or pathological in nature. Inadequate knowledge and improper vulva hygiene practices can increase the risk of pathological fluor albus. Objective: This study aimed to determine the differences in knowledge and attitudes of adolescent girls regarding vulva hygiene in the prevention of fluor albus before and after health education at MAN X Mojokerto Regency. Method: This study used a pre-experimental one-group pretest-posttest design involving 71 respondents selected through convenience sampling. Data were collected using validated and reliable knowledge and attitude questionnaires and analyzed using the Wilcoxon Signed-Rank Test. Result and Discussion: The average knowledge score increased from 67.96 in the pre-test to 84.15 in the post-test, while the average attitude score increased from 69.42 to 80.51. The Wilcoxon Signed -Rank Test showed significant differences in adolescent girls' knowledge and attitudes regarding vulva hygiene in prevention of fluor albus before and after health education intervention (p < 0.001). Conclusions: Significant differences observed in adolescent girls’ knowledge  were and attitudes regarding vulva hygiene in the prevention of fluor albus before and after health education.